2009
DOI: 10.2217/whe.09.19
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Organ Prolapse and Relationship with Skeletal Integrity

Abstract: Health burden related to osteoporotic fractures in an aging female population far exceeds that imposed by other chronic disorders such as cardiovascular disease and breast cancer. Bone mineral density assessment and clinical risk factors provide independent insights into fracture risk in individuals. A finite list of clinical risk factors are identified as prognostic of fracture risk, namely among aging women, including low body mass, compromised reproductive physiology (e.g., prolonged periods of amenorrhea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(62 reference statements)
0
5
1
1
Order By: Relevance
“…[1,1014] A correlation has been shown between skeletal fragility and POP in postmenopausal women. [15,16]…”
Section: Introductionmentioning
confidence: 99%
“…[1,1014] A correlation has been shown between skeletal fragility and POP in postmenopausal women. [15,16]…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about additional risk factors for reduced bone mineral density (BMD) may further improve the identification of individuals at increased risk of fractures. Pelvic floor disorders (PFDs), including pelvic organ prolapse (POP), urinary incontinence and anal incontinence, are common conditions in women, and it has been hypothesized that PFDs and low BMD may represent manifestations of a generalized disturbance in collagen metabolism [7]. Based on this hypothesis, previous studies have investigated the association between PFDs and reduced bone quantity or quality [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic floor disorders (PFDs), including pelvic organ prolapse (POP), urinary incontinence and anal incontinence, are common conditions in women, and it has been hypothesized that PFDs and low BMD may represent manifestations of a generalized disturbance in collagen metabolism [7]. Based on this hypothesis, previous studies have investigated the association between PFDs and reduced bone quantity or quality [7][8][9][10][11][12]. However, these studies provided conflicting results, and often included participants undergoing osteoporotic evaluation in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the similarity in the pathophysiology of two diseases, we hypothesized that there is an association between menopause and an increased risk of POP and osteoporosis. Some studies have identified the relationship between POP and skeletal compromise in postmenopausal women [13][14][15][17][18][19][20]. However, to our knowledge, no large-scale studies have been conducted on the relationship between POP and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%